The Effect of Competitiveness and Efficiency on the Added Value of the Copra Industry (ISIC 10421) in Indonesia - Apriani, Deassy; Putri, Gita Yulia; Teguh, Muhammad; Robiani, Bernadette (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2023)
Industry copra in Indonesia still not yet get attention in a manner specifically by the government so that causing export copra experience that level fluctuate. So from that importance role performance in the industry copra in development a country and for fulfil need society. This study aims to find out the competitiveness, level of efficiency and the influence of competitiveness and efficiency on the added value of the copra industry (ISIC 10421) in Indonesia. The type of data used is secondary data obtained from the Central Statistics Agency and UN Comtrade related to the copra industry in the 2011-2020 period. This research, using competitiveness analysis with the Revealed Comparative Advantage method, and multiple linear regression. The results showed that variable competitiveness of Indonesia has the strength of competitiveness and comparative induction in the copra industry, as evidenced by the calculation of the method Revealed Comparative Advantage which has a value of 27.36. The efficiency of the copra industry is fairly inefficient with the average level of efficiency obtained is 0.83. Meanwhile, variable competitiveness and efficiency have a positive and significant effect on the added value of the copra industry.